Perencanaan Tata Ruang Terbuka Hijau Sesuai Peraturan Daerah Kota Denpasar Nomor 27 Tahun 2011 - Ni Kadek Tisna Aristya Dewi; I Putu Gede Seputra; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
The declining quality and quantity of green open space in urban areas has caused a decrease in the quality of the environment. Therefore, it is necessary to conduct a research on the Green Open Spatial Planning, especially in Denpasar City the legal provisions of which has been regulated in Regional Regulation No. 27 of 2011. This research analyzes the planning for the use of Green Open Spatial and the mechanism for changing the Green Open Spatial to change its function to become Spatial Settlement. The method used in this research was a normative research method, in which legal data collection was carried out by recording library studies, document studies, information and explanations obtained both from the Laws, Government Regulations and other Regulations that can be further examined which related to this problem. Data analysis in this research was carried out systematically by classification of legal materials to facilitate the analysis work, then Legal materials obtained are then subjected to discussion and grouping into certain sections. The results found that the Green Open Space is an area dominated by plants that are built for protection functions. The pattern of spatial use as a basis for the Denpasar City Government sets Green Open Spaces namely Settlements and Public Facilities. Changes in the pattern of utilization of green open spaces have changed the function resulting in the realization of optimal urban spatial planning. This happened because of the weak awareness of the people of Denpasar City.